The Effect of Pursed Lip Breathing and Orthopneic Position on Increasing Peak Expiration Flow in Chronic Obstructive Pulmonary Disease Patients - Nava Hanantari; Novita Kurnia Wulandari; Maria Wisnu Kanita (JURNAL KEPERAWATAN MERSI, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a condition characterized by chronic respiratory symptoms, including shortness of breath and cough, decreased Peak Expiratory Flow (PEF), caused by airway obstruction. Interventions such as Pursed Lip Breathing and orthopnea positioning can potentially improve PEF in COPD patients. Objective: This study aims to analyze the effect of Pursed Lip Breathing and orthopnea position on increasing PEF in COPD patients at Kartini Karanganyar Hospital. Methods: This study used a quasi-experimental design with a pretest-posttest approach. The sample consisted of 64 COPD patients who were divided into two groups: the intervention group who received Pursed Lip Breathing and orthopnea position every morning for 5 minutes for 3 days, and the control group who only received the intervention according to hospital standards. PEF measurements were taken before and after the intervention using a Peak Flow Meter. Results: The results showed that the combination of the two interventions had a significant effect on increasing the patient's PEF indicating an improvement in respiratory function (p=0.00). Conclusion: Pursed Lip Breathing and orthopnea positioning are effective in improving PEF in COPD patients, so it can be recommended as part of respiratory care.